Calibration of the energy response matrix for X-ray detector CCD236. (20th May 2021) - Zhu, Y.X.; Lu, J.B.; Li, X.B.; Liu, X.Y.; Cui, W.W.; Han, D.W.; Wang, J.; Wang, Y.S.; Zhao, X.F.; Zhang, S.; Wang, G.F.; Chen, Y.P.; et al.
Abstract: CCD236 is a new generation swept charge device (SCD) developed by e2v. It is designed for the Low Energy Telescope (LE) onboard the Hard X-ray Modulation Telescope (HXMT). The spectrum of the detector is a convolution result of the incident spectrum and the energy response of the detector. One can obtain accurate quantities of incident spectrum by fitting the model spectrum with the energy response. According to the two-dimensional interpolation method, an energy response matrix of CCD236 is generated using the calibration data obtained by the low X-ray calibration facility located at Institute of High Energy Physics. The accuracy of interpolation is better than 0.2 eV, and the full width at half maximum (FWHM) variation trend with energy of the RSP agrees well with that of the calibration data. After that, a double-gaussian model of Fe-55 source was convoluted with the energy response matrix. The result shows that the fitting residual is controlled within 3σ after considering a systematic error of 0.1%. The deviation of full-energy peak is less than 10 eV. The RSP can well characterize the response of CCD236 detector in the observable energy region.